Management of wheat rusts-a revised strategy for gene deployment - and K.D. SRIVASTAVA, P. BAHADUR, D.V. SINGH (Indian Phytopathology, 2002)
Based on the available knowledge of adult plant resistance and vertical resistance, a revised strategy for managing stem 'and leaf rusts of wheat in 6 different ecological areas of India along the Puccinia path has been suggested. In areas 1 and 6, use of horizontal resistance/slow rusting varieties has been re-advocated as recommended earlier. Among the gene combinations recommended for the management of stem rust earlier for different areas, an addition of Sr2 in area 2; Sr2 and Sr26 in area 3; Sr2 and Sr3i in area 4 and Sr2 and Sr24 in area 5 shall be useful. For leaf rust management, addition of Lr /3 in area 2; Lr 19 and Lr23 in area 3; Lr34 and Lr26 in area 4 and Lr24 in area 5 shall further curtail leaf rust when added to gene combinations recommended earlier.